ANALISIS SISTEM KOMPENSASI FINANSIAL LANGSUNG DAN TIDAK LANGSUNG TERHADAP KINERJA KARYAWAN : Studi Kasus pada PT. Prima Multi Peralatan Medan - Luthfiah Nur Bayani; Aisyah, Siti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out how the direct and indirect financial compensation system is and how it affects performance; in this article explains how companies provide direct and indirect financial compensation, then also explains how the compensation system that has been carried out on employee performance is based on interviews with human resource division staff at PT. Prima Multi Equipment. The research methodology used in this research is descriptive qualitative interview technique with 2 staff of the company's human resources division, with a research time of 1 month starting from January-February 2022. As for the results of this study, it was found that the company was quite good at implementing a delivery system compensation for their workers, in the dialogue interviews conducted, the staff stated that all of these systems are still based on labor law regulations so that the compensation provided is fair according to government regulations; then from the compensation system that is carried out choosing a good influence on employee performance by obtaining information that the performance of the company's employees so far has been quite good as a whole from each site with minimal complaints about performance that is not optimal, always disciplined and always working to reach targets not only it turns out that from the results of the performance of the company's employees get an increased profit this year from the many achievements of the work that has been done by workers.